The impact of capital market on the economic growth in Oman - Md. Shabbir Alam; Muawya Ahmed Hussein (Financial Studies, 2019)
This paper investigated the effect of capital market on Omani economic growth using real Gross Domestic Product (GDP) as representative for economic growth. The main objective of the paper is to scan the impact of Muscat Security Market (MSM) on economic g rowth in Oman. The data were collected from the different official MSM annual reports, Central Bank of Oman annual reports and the World Bank Development Reports. The technique applied involved the use of multiple regression analysis to find the influence of the capital market on the Omani GDP. The analysis so far confirmed that there is a positive relationship between capital market and economic growth in Oman for the investigated period. So, it is recommended that, Oman should place gr eater emphasis on fi nancial sector development with special focus on capital market development to ensure economic growth.
Keywords: E2; E5; E6; G1; 330; Muscat security market (MSM); Capital market; GDP; Central Bank of Oman